Factors that influence in musculoskeletal injuries in the premises of the Central Market of Cartago, Costa Rica - Villalobos-Rodríguez, Ara (2020)
The muscular- skeletal injuries have a considerable cost for the public health[1], which is why the objective of the project was to contribute to the improvement of the work environment in the small and medium-sized enterprises, through the determination of the factors that influence in the muscular-skeletal injuries in manual handling of heavy loads operations. For it, the MAC method and measurement equipment like dynamometers and Polar watches were used to determine if the weight, distance, shape and size of the loads were a risk factor. The results reveal that the tasks of transportation, lifting and accommodation of the products were classified as critical risk, caused by incorrectly handling, the main risk detected was the biomechanical, derived of inadequate and prolonged positions, narrow corridors and small establishments; this added to the personal characteristics like low physical activity, and in the way the tasks are done wherein predominate the dynamic muscular effort. With this information the Central Market of Cartago, can make a risks evaluation in detail, also allow to adopt necessary measures regarding the formation of working methods and technical means appropriate in transport and load handling.